The table work for Casa-Grande by Nelson Rodrigues (Olhares, 2015)
The table work in the process of investigation about memory and the ficcional masterpiece, developed by the actors of the ensemble “Os Fofos Encenam”. The dramatic and scenic construction in the collaborative work. This anlaysis was made during the creation of the spectacle Memória da cana, based on the text Álbum de família, by Nelson Rodrigues, and inspired by the vision of the Brazilian patriarchal family from the novel Casa-Grande e Sensala, by Gilberto Freyre.
Keywords: Tabel work; Field research; Memory; Character creation; Collaborative Process; Photo memory